ṬABAṬABA’I INTERPRETATION ON PROPHETIC MISSION IN TAFSIR AL-MIZAN FOR THE CONSTRUCTION OF NUSANTARA SPIRITUAL CIVILIZATION - Achmad Achmad; Fadhlu Rahman; Pia Nuraripah (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2020)
Modernism as the product of Renaissance has succeeded in couping the reality of God. The view of several western intellectuals have caused to the obscurity of human concepts which then affects to the meaning of the progress of human civilization, and further, presents serious problems almost in all social life. In the context of the archipelago (Nusantara), some Islamists groups try to establish a civilization based on materialistic point of view and with textual interpretation of the Qur'an. In fact, Islam in the archipelago genealogically has characteristics which are very spiritual so it is not appropriate to develop an advanced civilization in the archipelago based on materialist achievements as promoted by western modernism. The prophetic mission interpreted by Ṭabaṭaba’i in al-Mīzān fī Tafsīr al-Qur'an verses 1-2 and 5 gives the concept of spiritual civilization based on the Qur'an which is in line with the character of the archipelago. Thus, this study seeks to answer these research questions: first, how is the prophetic mission interpreted by Ṭabaṭaba’i in his Tafsīr al-Mīzān constructing spiritual civilization? Second, how is the construction of spiritual civilization in harmony and able to actualize the treasury of the archipelago? The method used in this study is a descriptive analysis with the approach of Ṭabaṭaba’i’s interpretation (Tafsīr) on the prophetic mission. The study finds that Ṭabaṭaba’i interpretation on the Surah al-Jumu’ah verses 1-2 and 5 gives the spiritual construction of civilization that is in line with the character of the archipelago